Extracorporeal Membrane Oxygenation and Modern Detoxification Techniques in a Puerpera with Viral and Bacterial Pneumonia Caused by Flu A(H1N1) Virus - R. A. Kornelyuk; D. L. Shukevich; B. L. Hayes; L. E. Shukevich; S. V. Vostrikov; E. V. Grigoriev; G. P. Plotnikov (Общая реаниматология)
Outbreaks of viral infections have become a global healthcare challenge over the last decade. The 2009—2010 flu A (H1N1) outbreak resulted in global pandemia, associated with high morbidity and mortality reaching 31%. Another flu A (H1N1) outbreak occurred in 2015—2016. There is a strong probability that it may be repeated in the future. This infection is associated with its high incidence among pregnant women. There are some published reports describing the efficacy and safety of veno%venous extracorporeal membrane oxygenation (ECMO) in patients with severe acute respiratory distress syndrome that is refractory to standard therapeutic options. The article presents a clinical case of a successful use of extracorporeal membrane oxygenation and intermittent renal replacement therapy in a puerpera with acute respiratory distress syndrome caused by flu A (H1N1)-related severe viral and bacterial pneumonia. The positive effects of the combination of veno%venous extracorporeal membrane oxygenation and modern detoxification techniques have been demonstrated. Revealed organizational problemswere related to selection criteria for prescription of extracorporeal gas exchange, as well as to carrying out the procedure in an institution in the deficiency of the experienced staff and corresponding equipment.